Implementasi Metode Kisah Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Sejarah Kebudayaan Islam Di Kelas Vii Pondok Pesantren Al-Ikhwan As-Salam Serapuh Abc - Siti Zulaiha; Diani Syahfitri; Nurmisda Ramayani (Jurnal Berbasis Sosial, 2022)
The acquisition of student learning outcomes in islamic cultural history subjects is relatively low. This is because the level of understanding of students to the material delivered by teachers is also low. The low level of student understanding of the material delivered by the teacher can be influenced by several factors.One of them is the lack of interesting explanations from teachers. The teacher does not master the material, the teacher explains the material while reading without using methods. As a result, learning is ineffective. Lack of learning resources, learners only get one for two people only so students copy all the material as a result of a lot of wasted time.Because of this background, the improvement of learning through classroom action research is carried out with the aim to improve students' learning outcomes in learning the history of Islamic culture through the method of story in class VII-3 at Pondok Pesantren Al-Ikhwan As-Salam Serapuh Abc.The study was conducted in three stages: pre-cycle, cycle I, and cycle II. Learning data is obtained individually and classically after planning, action, elevation and reflection. In the pre-cycle of student completion by 25% (9 people), in cycle I student completion by 58% (21 people), and cycle II student completion increased to 88% (32 people). Thus there is an increase in student learning outcomes on each cycle.